Analysis of the timing of endoscopic treatment for esophagogastric variceal bleeding in cirrhosis - Wu, Kaini; Fu, Yunfeng; Guo, Zixiang; Zhou, Xiaodong (Frontiers in Medicine, 2022)
Background: Existing guidelines recommend endoscopic treatment within 12 hours or 12-24 hours for patients with esophagogastric variceal bleeding (EGVB) in cirrhosis. In addition, research findings on the optimal time for endoscopy are inconsistent. Aims: To investigate the relationship between the timing of endoscopy and clinical outcomes in cirrhotic patients with EGVB and to analyze the risk factors for the composite outcomes after endoscopic treatment. Methods: From January 2019 to June 2020, 456 patients with cirrhotic EGVB who underwent endoscopy were matched by a 1:1 propensity score. Finally, 266 patients were divided into two groups, including 133 patients within 12 hours (urgent endoscopy group) of admission and after 12 hours (non-urgent endoscopy group). Baseline data and clinical outcomes were compared. Logistic regression model analysis was used to determine risk factors for 30-day rebleeding and mortality. Results: In 266 patients, the overall 30-day rebleeding rate and mortality were 10.9% (n = 29) and 3.4% (n = 9), respectively. Patients who underwent endoscopic treatment within 12 hours had significantly higher 30-day rebleeding outcomes than those who underwent treatment beyond 12 hours (15% vs. 6.8%, p = 0.003). However, 30-day mortality did not differ significantly between the two groups (3% vs. 3.8%, p = 0.736). Logistic regression analysis showed that age and shock on admission were independent risk factors for the composite outcome of 30-day rebleeding and mortality in patients with EGVB. Conclusion: The 30-day rebleeding rate in patients with cirrhotic EGVB treated with urgent endoscopy was significantly higher than that in patients treated with non-urgent endoscopy, but there was no significant difference in 30-day mortality.